Gallium nitride substrate polishing solution based on Fenton-like oxidation technology

By using nanometal suspension as a catalyst in the gallium nitride substrate polishing liquid, the activation of oxidant generates strong oxidative free radicals, solving the problems of surface damage and short catalyst life during the gallium nitride substrate polishing process, achieving high efficiency, Low-cost gallium nitride substrate surface treatment expands its application range.

CN119242183APending Publication Date: 2025-01-03BEIJING HANGTIAN SAIDE TECH DEV CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411373690.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing gallium nitride substrate polishing liquid has surface/subsurface damage, short catalyst life, high cost and difficulty in commercial production during chemical mechanical polishing, which limits the development of gallium nitride components.

Method used

Using gallium nitride substrate polishing liquid based on Fenton-like oxidation technology, the nanometal suspension is added as a solid phase catalyst, and the high surface area and rich pore structure of nanometals are used to activate the oxidant to generate strong oxidative free radicals and achieve nitriding. Ultra-smooth polishing of the surface of the gallium substrate.

Benefits of technology

It significantly improves the characteristics of the surface of the gallium nitride substrate, ensures that it is ultra-smooth and defect-free, with a surface roughness below 0.2nm, meets industrial requirements, expands the application range of gallium nitride components, and reduces costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a gallium nitride substrate polishing solution based on a Fenton-like oxidation technology. The gallium nitride substrate polishing solution comprises the following raw materials in percentage by mass: 10-40% of a polishing abrasive, 5-40% of a nano metal suspension, 0.1-10% of a complexing agent, 0.1-10% of an oxidizing agent and the balance of deionized water. The nano-metal suspension liquid is a nano zero-valent metal suspension liquid or a nano bimetal suspension liquid formed by doping two metals. The particle size range of metal in the nano-metal suspension liquid is 60-100 nm. According to the polishing solution disclosed by the invention, the surface characteristics of the gallium nitride substrate are greatly improved by adding the nano-metal and based on a solid-phase catalysis technology of the nano-metal, so that the surface of the gallium nitride substrate is ultra-smooth and has no defects, no surface / subsurface damage and no surface roughness Rult after the polishing solution is used; therefore, the industrialization requirement of the gallium nitride as a photoelectric device is met, and the application range of the gallium nitride component is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor substrate material polishing, and in particular to a gallium nitride substrate polishing liquid based on a Fenton-like oxidation technology. Background Art

[0002] From the first generation of semiconductor materials to the third generation of semiconductor materials, the performance has been continuously improved. In the field of chip manufacturing, the third generation of semiconductor materials are more resistant to temperature and high pressure than the first generation of semiconductors due to their advantages such as high bandgap width. They are increasingly used in the field of chip reliability. The development of smart phones has driven the development of the fast charging field. The use of third generation semiconductors as the core module of mobile phone charging can increase the working efficiency by at least 10% compared with the second generation of semiconductor materials, significantly improving the working efficiency of charging. With the development of third generation semiconductor materials, it has expanded from the microelectronics industry to popular research fields such as lighting, communications, energy, and 5G, playing an increasingly important role in industrial production and promoting energy conservation and emission reduction.

[0003] In order to achieve a low environmental load and energy-saving society, the next generation of optoelectronic devices based on gallium nitride (GaN) has attracted much attention. Gallium nitride crystals are third-generation semiconductor materials with excellent properties such as large bandgap, high lattice matching, high critical breakdown field strength, high electron mobility, and high thermal conductivity. They have broad application prospects in blue light lighting, high temperature, high frequency, and radiation-resistant devices. At present, the use of gallium nitride in the field of blue light lighting is relatively mature, but in precision fields such as chips, its surface quality and various indicators are very high. Therefore, it is very meaningful to study the surface flattening processing technology of gallium nitride crystals.

[0004] As an electronic component material, the surface quality of GaN substrate directly affects the performance of electronic devices. To ensure the use requirements of GaN in actual processing, the surface of GaN substrate is required to be ultra-smooth, defect-free, and free of surface / subsurface damage, with a surface roughness below the nanometer level (industrial requirements Ra < 0.2nm). However, GaN crystals are hard, with a Mohs hardness of 8, are highly brittle, and have chemical properties that are resistant to acid and alkali corrosion. There are great difficulties in the chemical mechanical polishing process, which greatly restricts the development of GaN components. How to reduce surface / subsurface damage and improve polishing quality and processing efficiency in the ultra-precision polishing of GaN substrates is a key issue that needs to be solved in the application and development of GaN components.

[0005] The main problems in the precision polishing of GaN substrates are:

[0006] (1) Fe generated based on traditional Fenton catalytic reaction technology 3+ It is easy to form precipitation. In order to prevent the formation of iron sludge precipitation, it is often necessary to limit the pH to an acidic level less than 3. Long-term exposure to acidic conditions is harmful to both equipment and human body.

[0007] (2) New technologies such as ion beam, magnetorheological, and electro-Fenton are not yet stable or have high costs, making them difficult to commercialize.

[0008] (3) The catalyst of traditional Fenton oxidation technology has a short service life and its catalytic ability decreases significantly during the polishing process, which is not conducive to long-term processing of the polishing liquid.

[0009] It can be seen that the above existing gallium nitride substrate polishing liquid still has shortcomings and needs to be further improved. How to create a new gallium nitride substrate polishing liquid based on Fenton-like oxidation technology to greatly improve the surface properties of gallium nitride substrates and expand the application range of gallium nitride components has become a goal that the industry urgently needs to improve. Summary of the invention

[0010] The technical problem to be solved by the present invention is to provide a gallium nitride substrate polishing liquid based on Fenton-like oxidation technology, which greatly improves the surface properties of the gallium nitride substrate by adding nanometals, provides a reliable guarantee for expanding the application range of gallium nitride components, and thus overcomes the shortcomings of existing gallium nitride substrate polishing liquids.

[0011] In order to solve the above technical problems, the present invention provides a gallium nitride substrate polishing liquid based on Fenton-like oxidation technology, comprising the following raw materials in percentage by mass: 10-40% polishing abrasive, 5-40% nano-metal suspension, 0.1-10% complexing agent, 0.1-10% oxidant, and the rest is deionized water.

[0012] As a further improvement, the nano metal suspension is a nano zero-valent metal suspension.

[0013] As a further improvement, the nano zero-valent metal suspension includes one or more transition metals selected from the group consisting of nano iron, nano copper, nano aluminum, and nano vanadium.

[0014] As a further improvement, the nano-metal suspension is a nano-bimetal suspension doped with two metals.

[0015] As a further improvement, the nano bimetallic suspension is a copper-vanadium bimetallic suspension.

[0016] As a further improvement, the metal particle size range in the nano-metal suspension is 60-100 nm.

[0017] As a further improvement, the polishing abrasive is one or more of silicon oxide, cerium oxide, aluminum oxide, and iron oxide, and the abrasive particle size range is 80-120 nm.

[0018] As a further improvement, the complexing agent is a polyphosphate including one or more of dipolyphosphate, tripolyphosphate and hexametaphosphate.

[0019] In a further improvement, the oxidant is one or more of sodium hypochlorite, hydrogen peroxide, potassium peroxide, sodium persulfate, and urea peroxide.

[0020] As a further improvement, the applicable pH range of the gallium nitride substrate polishing solution is 2-11.

[0021] The present invention adds a flowable solid phase suspension catalyst, a nano-metal suspension, into the polishing liquid, and utilizes the characteristics of nano-metals with large specific surface area, high surface energy, and rich pore structure to activate the oxidant to produce free radicals with strong oxidizing properties, that is, to replace the Fe in the traditional Fenton reagent. 2+ To catalyze the decomposition of H2O2 to produce ·OH, a soft oxide layer is quickly formed on the surface of the GaN substrate, thereby achieving the purpose of rapid removal under the action of polishing abrasives.

[0022] After adopting such a design, the present invention has at least the following advantages:

[0023] The gallium nitride substrate polishing liquid based on the Fenton-like oxidation technology of the present invention greatly improves the surface properties of the gallium nitride substrate by adding nano-metals and based on the solid-phase catalysis technology of nano-metals, so that the surface of the gallium nitride substrate is ultra-smooth, defect-free, and free of surface / subsurface damage after use, and the surface roughness Ra is less than 0.2nm, which meets the industrialization requirements of gallium nitride as an optoelectronic device and expands the application range of gallium nitride components.

[0024] The gallium nitride substrate polishing liquid of the present invention has a pH application range of 2-11, has a wide application range, and has excellent use conditions, which is conducive to popularization and use; and the nano-metal solid-phase catalyst in the polishing liquid is convenient to recover, can be repeatedly used, and reduces costs. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is described in detail below through specific embodiments, and the specific embodiments are as follows:

[0026] Example 1

[0027] The raw materials of the polishing liquid in this embodiment are as follows:

[0028] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0029] The nano-metal suspension uses 80nm zero-valent nano-copper suspension with a mass percentage of 40%;

[0030] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0031] The oxidant is 30% hydrogen peroxide, with a mass percentage of 10%.

[0032] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 1 is obtained after the mixture is evenly mixed.

[0033] Example 2

[0034] The raw materials of the polishing liquid in this embodiment are as follows:

[0035] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0036] The nano-metal suspension uses 80nm zero-valent nano-copper suspension with a mass percentage of 40%;

[0037] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0038] The oxidant is a 10% sodium persulfate solution with a mass percentage of 10%.

[0039] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 2 is obtained after the mixture is evenly mixed.

[0040] Example 3

[0041] The raw materials of the polishing liquid in this embodiment are as follows:

[0042] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0043] The nano-metal suspension uses a 0.3 μm zero-valent copper suspension with a mass percentage of 40%;

[0044] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0045] The oxidant is 30% hydrogen peroxide, with a mass percentage of 10%.

[0046] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 3 is obtained after the mixture is evenly mixed.

[0047] Example 4

[0048] The raw materials of the polishing liquid in this embodiment are as follows:

[0049] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0050] The nano-metal suspension uses a 0.3 μm zero-valent copper suspension with a mass percentage of 40%;

[0051] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0052] The oxidant is a 10% sodium persulfate solution with a mass percentage of 10%.

[0053] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 4 is obtained after the mixture is evenly mixed.

[0054] Example 5

[0055] The raw materials of the polishing liquid in this embodiment are as follows:

[0056] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0057] The nano-metal suspension uses a 90nm zero-valent nano-iron suspension with a mass percentage of 40%;

[0058] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0059] The oxidant is 30% hydrogen peroxide, with a mass percentage of 10%.

[0060] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 5 is obtained after the mixture is evenly mixed.

[0061] Example 6

[0062] The raw materials of the polishing liquid in this embodiment are as follows:

[0063] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0064] The nano-metal suspension uses a 90nm zero-valent nano-iron suspension with a mass percentage of 40%;

[0065] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0066] The oxidant is a 10% sodium persulfate solution with a mass percentage of 10%.

[0067] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 6 is obtained after the mixture is evenly mixed.

[0068] Example 7

[0069] The raw materials of the polishing liquid in this embodiment are as follows:

[0070] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0071] The nano-metal suspension uses 80nm nano-copper-vanadium bimetallic suspension with a mass percentage of 40%;

[0072] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0073] The oxidant is 30% hydrogen peroxide, with a mass percentage of 10%.

[0074] Among them, the preparation method of 80nm nano copper-vanadium bimetallic suspension adopts thermal precipitation method, that is, a certain amount of ethylene glycol is heated to 80℃ in a container, and then NH4VO3 and Cu(NO3)2·3H2O are added in proportion, keeping the molar ratio of the two at 1:1, stirring for 30min, and finally adding an appropriate amount of sodium acetate as a precipitant, and transferring to a polytetrafluoroethylene reactor. Keep warm at 200℃ for 24h. Collect the solid product, wash it with ultrapure water and ethanol, and then use nano-crushing equipment to crush the copper-vanadium bimetallic solid into 80nm particles, and finally add the crushed particles into a liquid containing a suspending agent, and use an ultrasonic device to evenly disperse the nanoparticles into the suspension. Among them, the suspending agent is one or more of polyvinyl pyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.

[0075] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 7 is obtained after the mixture is evenly mixed.

[0076] Example 8

[0077] The raw materials of the polishing liquid in this embodiment are as follows:

[0078] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0079] The nano-metal suspension uses 80nm nano-copper-vanadium bimetallic suspension with a mass percentage of 40%;

[0080] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0081] The oxidant is a 10% sodium persulfate solution with a mass percentage of 10%.

[0082] Wherein, the preparation method of nano copper-vanadium bimetallic suspension is the same as that in Example 7.

[0083] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 8 is obtained after the mixture is evenly mixed.

[0084] Example 9

[0085] The raw materials of the polishing liquid in this embodiment are as follows:

[0086] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0087] The nano-metal suspension uses a 0.3 μm copper-vanadium bimetallic suspension with a mass percentage of 40%;

[0088] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0089] The oxidant is 30% hydrogen peroxide, with a mass percentage of 10%.

[0090] Among them, the preparation method of 0.3μm copper-vanadium bimetallic suspension adopts the existing thermal precipitation method, that is, a certain amount of ethylene glycol is heated to 80°C in a container, and then NH4VO3 and Cu(NO3)2·3H2O are added in proportion, keeping the molar ratio of the two at 1:1, stirring for 30 minutes, and finally adding an appropriate amount of sodium acetate as a precipitant, and transferring to a polytetrafluoroethylene reactor. Keep warm at 200°C for 24 hours. Collect the solid product, wash it with ultrapure water and ethanol, and then use a crushing device to crush the copper-vanadium bimetallic solid into 0.3μm particles, and finally add the crushed particles to a liquid containing a suspending agent, and use an ultrasonic device to evenly disperse the particles into the suspension. Among them, the suspending agent is one or more of polyvinyl pyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.

[0091] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 9 is obtained after the mixture is evenly mixed.

[0092] Example 10

[0093] The raw materials of the polishing liquid in this embodiment are as follows:

[0094] The polishing abrasive uses silicon dioxide with a particle size of 100 nm and a mass percentage of 40%;

[0095] The nano-metal suspension uses a 0.3 μm copper-vanadium bimetallic suspension with a mass percentage of 40%;

[0096] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0097] The oxidant is a 10% sodium persulfate solution with a mass percentage of 10%.

[0098] Wherein, the preparation method of the copper-vanadium bimetallic suspension is the same as that of Example 9.

[0099] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 10 is obtained after the mixture is evenly mixed.

[0100] Embodiment 11

[0101] The raw materials of the polishing liquid in this embodiment are as follows:

[0102] The polishing abrasive uses silicon dioxide with a particle size of 120nm and a mass percentage of 40%;

[0103] The nano-metal suspension uses a 90nm nano-iron-vanadium bimetallic suspension with a mass percentage of 40%;

[0104] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0105] The oxidant is 30% hydrogen peroxide, with a mass percentage of 10%.

[0106] Among them, the preparation method of 90nm nano iron-vanadium bimetallic suspension adopts the existing thermal precipitation method, that is, a certain amount of ethylene glycol is heated to 80°C in a container, and then NH4VO3 and Fe(NO3)3·9H2O are added in proportion, and the molar ratio of the two is kept at 1:1, stirred for 30 minutes, and finally an appropriate amount of sodium acetate is added as a precipitant, and transferred to a polytetrafluoroethylene reactor. Keep warm at 200°C for 24 hours. Collect the solid product, wash it with ultrapure water and ethanol, and then use a crushing device to crush the iron-vanadium bimetallic solid into 90nm particles, and finally add the crushed particles to a liquid containing a suspending agent, and use an ultrasonic device to evenly disperse the particles into the suspension. Among them, the suspending agent is one or more of polyvinyl pyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.

[0107] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 11 is obtained after the mixture is evenly mixed.

[0108] Example 12

[0109] The raw materials of the polishing liquid in this embodiment are as follows:

[0110] The polishing abrasive uses silicon dioxide with a particle size of 120nm and a mass percentage of 40%;

[0111] The nano-metal suspension uses a 90nm nano-iron-vanadium bimetallic suspension with a mass percentage of 40%;

[0112] The complexing agent is sodium dipolyphosphate, with a mass percentage of 10%;

[0113] The oxidant is a 10% sodium persulfate solution with a mass percentage of 10%.

[0114] Among them, the preparation method of 90nm nano iron-vanadium bimetallic suspension is the same as Example 11.

[0115] The steps for preparing the polishing liquid are as follows: the polishing abrasive, nano-metal suspension, complexing agent and oxidant in the above mass ratio are mixed under constant stirring, and the polishing liquid 12 is obtained after the mixture is evenly mixed.

[0116] Application Examples

[0117] The polishing liquid 1-12 obtained in the above-mentioned embodiment 1-12 was used to polish the gallium nitride substrate material. The polishing equipment used was Jinyan KD15B, and the polishing pressure was 350g / cm 2 , the polishing speed is 70rpm, and the polishing liquid flow rate is 70ml / min.

[0118] After polishing, the gallium nitride was cleaned and dried. The removal rate was then calculated using a weighing method, and the surface roughness Ra of the gallium nitride was measured using an atomic force microscope. The results are shown in Table 1 below.

[0119] Table 1 Removal rate and surface roughness results of each polishing liquid for polishing gallium nitride substrate material

[0120] Example Polishing liquid Removal rate (nm / h) Ra(nm) 1 Polishing liquid 1 98 0.05 2 Polishing liquid 2 60 0.07 3 Polishing liquid 3 18 0.18 4 Polishing liquid 4 10 0.3 5 Polishing liquid 5 95 0.07 6 Polishing liquid 6 75 0.08 7 Polishing liquid 7 102 0.05 8 Polishing liquid 8 98 0.08 9 Polishing liquid 9 20 0.2 10 Polishing liquid 10 14 0.25 11 Polishing liquid 11 105 0.06 12 Polishing liquid 12 95 0.09

[0121] From Table 1 above, it can be seen that the polishing liquid using a nano-metal suspension with a metal particle size of less than 100nm as a catalyst has a higher polishing rate and better surface quality for the polishing treatment of gallium nitride substrates, making the surface roughness Ra of gallium nitride lower than 0.09; while when a sub-nanometer or micron-level metal suspension is used as a catalyst, the polishing rate for the polishing treatment of gallium nitride substrates is lower, and the surface quality is poor or cannot meet the requirements. In addition, it can be seen that the polishing liquid using a nano-bimetallic suspension has a higher polishing rate for the polishing treatment of gallium nitride substrates than the polishing liquid using a nano-metal single substance. It can also be seen that the above-mentioned polishing liquid uses hydrogen peroxide as an oxidant, and the polishing rate for the polishing treatment of gallium nitride substrates is higher than the polishing rate using sodium persulfate as an oxidant, and the surface quality is also better.

[0122] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Those skilled in the art may make some simple modifications, equivalent changes or modifications using the technical contents disclosed above, which all fall within the protection scope of the present invention.

Claims

1. A gallium nitride substrate polishing liquid based on Fenton-like oxidation technology, characterized in that: The raw materials are composed of the following in percentage by mass: 10-40% of polishing abrasive, 5-40% of nano metal suspension, 0.1-10% of complexing agent, 0.1-10% of oxidant, and the rest is deionized water.

2. The gallium nitride substrate polishing liquid based on Fenton-like oxidation technology according to claim 1, characterized in that: The nano metal suspension is a nano zero-valent metal suspension.

3. The gallium nitride substrate polishing liquid based on Fenton-like oxidation technology according to claim 2, characterized in that: The nano zero-valent metal suspension includes one or more transition metals selected from the group consisting of nano iron, nano copper, nano aluminum, and nano vanadium.

4. The gallium nitride substrate polishing liquid based on Fenton-like oxidation technology according to claim 1, characterized in that: The nano metal suspension is a nano bimetallic suspension formed by doping two metals.

5. The gallium nitride substrate polishing liquid based on Fenton-like oxidation technology according to claim 4, characterized in that: The nano bimetallic suspension is a copper-vanadium bimetallic suspension.

6. The gallium nitride substrate polishing liquid based on Fenton-like oxidation technology according to any one of claims 1 to 5, characterized in that: The metal particle size range in the nano-metal suspension is 60-100 nm.

7. The gallium nitride substrate polishing liquid based on Fenton-like oxidation technology according to claim 6, characterized in that: The polishing abrasive is one or more of silicon oxide, cerium oxide, aluminum oxide, and iron oxide, and the abrasive particle size ranges from 80 to 120 nm.

8. The gallium nitride substrate polishing liquid based on Fenton-like oxidation technology according to claim 6, characterized in that: The complexing agent is a polyphosphate including one or more of dipolyphosphate, tripolyphosphate and hexametaphosphate.

9. The gallium nitride substrate polishing liquid based on Fenton-like oxidation technology according to claim 6, characterized in that: The oxidant is one or more of sodium hypochlorite, hydrogen peroxide, potassium peroxide, sodium persulfate, and urea peroxide.

10. The gallium nitride substrate polishing liquid based on Fenton-like oxidation technology according to claim 6, characterized in that: The applicable pH range of the gallium nitride substrate polishing liquid is 2-11.

Citation Information

Cited By

  • A polishing liquid for third-generation semiconductor gallium nitride and a preparation method thereof

    CN122750262A